Effectiveness of cyclosporine A in patients with moderate to severe plaque psoriasis in a real-life clinical setting in Italy: the TRANSITION study. (2nd January 2022) - Marsili, F.; Travaglini, M.; Stinco, G.; Manzoni, R.; Tiberio, R.; Prignano, F.; Mazzotta, A.; Cannavò, S. P.; Cuccia, A.; Germino, M.; Bongiorno, M. R.; Persechino, S.; et al.
Abstract: Background: Cyclosporine A (CsA) is one of the systemic therapeutic options for moderate-to-severe psoriasis, based on its efficacy and rapidity of action. The current study investigated the response to CsA in patients with moderate-to-severe plaque psoriasis. Materials and Methods: TRANSITION was an observational, cross-sectional, multicentre study which evaluated the proportion of partial- and suboptimal-responders among patients with moderate-to-severe plaque psoriasis treated with continuous CsA for ≥12 weeks. Patients demonstrating a Psoriasis Area and Severity Index (PASI) response of ≥90, ≥75 and <90, ≥50 and <75 and <50 were defined as responders, suboptimal-responders, partial-responders, and non-responders, respectively. Results: A total of 196 patients (mean age, 46.6 years; 62.8% males) from 14 sites in Italy were evaluated. At the study visit, the mean (SD) PASI score was 4.2(5.5) compared with 15.3(7.1) prior to the last CsA cycle. For response categories, 39.8%, 22.4%, 16.8%, and 20.9% of patients were responders, suboptimal-responders, partial-responders, and non-responders to CsA treatment. Overall, 28.6% of patients permanently discontinued treatment with CsA (lack of efficacy [10.2%], poor tolerability and voluntary discontinuation [3.6% each], and other [11.7%]). Conclusion: Patients were only partially satisfied with CsA treatment, reporting measurable impact on quality of life. Only 40% patients showed a satisfactory response to CsA.